New insight into the role of macrophages in ovarian function and ovarian aging - Tang, Maoxing; Zhao, Manzhi; Shi, Yuhua (Frontiers in Endocrinology, 2023)
Macrophages (MΦs) are the most abundant leukocytes in mammalian ovaries that have heterogeneity and plasticity. A body of evidence has indicated that these cells are important in maintaining ovarian homeostasis and they play critical roles in ovarian physiological events, such as folliculogenesis, ovulation, corpus luteum formation and regression. As females age, ovarian tissue microenvironment is typified by chronic inflammation with exacerbated ovarian fibrosis. In response to specific danger signals within aged ovaries, macrophages polarize into different M1 or M2 phenotypes, and specialize in unique functions to participate in the ovarian aging process. In this review, we will focus on the physiologic roles of MΦs in normal ovarian functions. Furthermore, we will discuss the roles of MΦs in the process of ovarian senescence, as well as the novel techniques applied in this field.